Analisa Manajemen Resiko Pada Bisnis Pembangunan dan Penjualan Perumahan - Tubagus Ahmad Darojat (Forum Kerjasama Pendidikan Tinggi, 2020)
Residential buildings are very high-risk occupations from the initial construction to the end, a lot of construction has terminated the project because the budget is not in accordance with the plan, which is caused by the company not careful in seeing the many aspects of risk that will occur if the project is developed starting from the aspect external (internal) and internal (internal) factors, it is necessary to analyze the development of housing projects in order to avoid various risks, ranging from the development of project development and business to sales, housing sales themselves are carried out using SWOT analysis to see the strengths of weaknesses and opportunities from housing sales, the results obtained business development projects and housing sales can proceed well and in sales further enhance marketing strategies that will achieve sales targets according to the strengths and opportunities of the strategic location of housing construction